Individual preparedness and response to chemical, radiological, nuclear, and biological terrorist attacks : the reference guide - Davis, Lynn E. (Lynn Etheridge), 1943- (RAND, Public Safety and Justice, 2003)
This reference guide summarizes the essential features of a strategy for what individuals should do to prepare for and respond to terrorist attacks involving chemical, radiological, nuclear, and biological weapons.